2021
DOI: 10.1186/s12933-021-01319-1
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-glucose index in the development of peripheral artery disease: findings from the Atherosclerosis Risk in Communities (ARIC) Study

Abstract: Background It remains unclear whether triglyceride-glucose (TyG) index, a surrogate marker of insulin resistance, is prospectively associated with incident peripheral arterial disease (PAD). Methods We included 12,320 Atherosclerosis Risk in Communities Study participants (aged 54.3 ± 5.7 years) free of a history of PAD at baseline (visit 1: 1987–1989). The TyG index was determined using ln (fasting triglycerides [mg/dL] × fasting glucose [mg/dL]/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 42 publications
1
24
1
Order By: Relevance
“…Therefore, the relationship between the TyG index and its longitudinal variation with cardiovascular outcomes in young populatoin needs to be evaluated. An analysis of the Atherosclerosis Risk in Communities (ARIC) Study [ 29 ], including 9097 participants in the analysis of TyG index trajectory groups and incident peripheral artery disease (PAD), have found that TyG index trajectories at highest levels had an greatest risk of future incident PAD. Thus, the measurement of the long-term trajectory of the TyG index could reflect the long-term impact of the TyG index on adverse health outcomes and provide more robust and reliable results.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the relationship between the TyG index and its longitudinal variation with cardiovascular outcomes in young populatoin needs to be evaluated. An analysis of the Atherosclerosis Risk in Communities (ARIC) Study [ 29 ], including 9097 participants in the analysis of TyG index trajectory groups and incident peripheral artery disease (PAD), have found that TyG index trajectories at highest levels had an greatest risk of future incident PAD. Thus, the measurement of the long-term trajectory of the TyG index could reflect the long-term impact of the TyG index on adverse health outcomes and provide more robust and reliable results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, compared with the HOMA-IR, TyG index showed better evaluation efficiency [ 26 , 27 ]. Among them, serum triglyceride and glucose are low-cost routine biochemical detection items [ 6 ], therefore, the immense advantage of using such a simple method of IR identification is obviously that it is easily accessible in any clinical settings and has a good application prospect [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the dynamic changes in TG, FBG, and therefore TyG index over time, the impact of longitudinal TyG index trends needs to be evaluated. In a recent study, Gao et al observed 4 distinct trajectories of the TyG index over 20 years, each associated with a different risk of future peripheral artery disease, with the two-decade trajectory with an elevated TyG index presenting the greatest risk [ 33 ]. However, little is known about the longitudinal variation of the TyG index and its association with subsequent arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%